2016
DOI: 10.1371/journal.pone.0157762
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Fluorescent Antibody-Drug Conjugate for Molecular Imaging and Targeted Therapy of Pancreatic Cancer

Abstract: Antibodies are widely available and cost-effective research tools in life science, and antibody conjugates are now extensively used for targeted therapy, immunohistochemical staining, or in vivo diagnostic imaging of cancer. Significant advances in site-specific antibody labeling technologies have enabled the production of highly characterized and homogenous conjugates for biomedical purposes, and some recent studies have utilized site-specific labeling to synthesize bifunctional antibody conjugates with both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 98 publications
0
37
0
Order By: Relevance
“…15 Polymer prodrugs indeed exhibit numerous advantages over traditional drug-loaded nanocarrier including absence of "burst release" (that is, the quick release post-administration of a significant fraction of the drug only adsorbed at the surface of the nanoparticles), enhanced drug loadings and drug solubility improvement. 16 The most extensively used strategy to produce Ptx-polymer prodrugs consists in the linkage of Ptx by post-functionalization to preformed polymers ("grafting to" method), such as polyethylene glycol (PEG), 17 poly(L-glutamic acid) (PGA), 18 polylactide (PLA), 19,20 dendrimer, 21,22 and other block polymers. [23][24][25] However, moderate conjugation efficacies, tedious multistep synthetic pathways and difficulty to accurately position the drug on the polymer chain were often witnessed.…”
Section: Introductionmentioning
confidence: 99%
“…15 Polymer prodrugs indeed exhibit numerous advantages over traditional drug-loaded nanocarrier including absence of "burst release" (that is, the quick release post-administration of a significant fraction of the drug only adsorbed at the surface of the nanoparticles), enhanced drug loadings and drug solubility improvement. 16 The most extensively used strategy to produce Ptx-polymer prodrugs consists in the linkage of Ptx by post-functionalization to preformed polymers ("grafting to" method), such as polyethylene glycol (PEG), 17 poly(L-glutamic acid) (PGA), 18 polylactide (PLA), 19,20 dendrimer, 21,22 and other block polymers. [23][24][25] However, moderate conjugation efficacies, tedious multistep synthetic pathways and difficulty to accurately position the drug on the polymer chain were often witnessed.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results indicated a strong affinity binding of h173‐Cy5.5 with high targeting specificity. Another research study reported the efficacy of a dual‐labelled fluorescent antibody‐drug conjugates (ADCs) for in vivo targeting of carcinoembryonic antigen (CEA) biomarker on positive pancreatic tumor cells (BxPC‐3) with high cytotoxicity and internalization kinetics . Research investigation by Keyaerts and team (2016) focused on generating a Ga‐HER2 (human epidermal growth factor receptor 2)‐nanobody as a molecular imaging probe for the diagnosis of breast cancers .…”
Section: Conventional Molecular Probes For Targeting Cancer Cellsmentioning
confidence: 99%
“…developed a dual‐labeled fluorescent antibody‐drug conjugate using a near‐infrared PEGylated fluorophore and theranostic antibody to specifically target pancreatic tumor cells for molecular imaging and targeted therapy. Research findings based on this technology displayed high cytotoxicity and effective internalization kinetics of the targeted BxPC‐3 pancreatic tumor cell line, indicating the effective performance of the dual‐labeled and bi‐functional fluorescent antibody‐drug complex in diagnosing, monitoring, and treating tumor cells simultaneously . Besides that, semiconductor quantum dots (QDs), which are luminescent materials with tunable optical and electrical features as well as fluorescence emission properties, are also gaining considerable attention in biological and chemosensory applications.…”
Section: Conventional Molecular Probes For Targeting Cancer Cellsmentioning
confidence: 99%
“…In addition to the rapidly expanding field of CEA-targeted anticancer therapeutics, several imaging agents have become available for clinical testing. These agents can be labeled with radioisotopes for positron emission tomography or single-photon emission computed tomography imaging,10,11 with near-infrared (NIR) fluorescent dyes,12,13 or they can provide both molecular imaging and targeted therapy of CEA-expressing tumors 14…”
Section: Introductionmentioning
confidence: 99%